KEPENTINGAN INDONESIA MEMUTUSKAN HUBUNGAN KERJA SAMA REDUCING EMISSIONS FROM DEFORESTATION AND FOREST DEGRADATION (REDD+) DENGAN NORWEGIA TAHUN 2021 - Selvia Ranti; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The REDD+ scheme is a climate change mitigation as an effort to reduce greenhouse gas emissions. REDD+ activities are environmental conservation and efforts to improve sustainable economies, as well as reforestation initiatives in deforested and degraded forest areas. Despite its many benefits, REDD+ schemes require a clear and more comprehensive framework to accommodate all aspects that can encourage more carbon storage transactions and wider integrated policy implementation. This study aims to examine the interests of Indonesia in terminating the Reducing Emissions from Deforestation and Forest Degradation (REDD+) Cooperation with Norway in 2021. The author uses a neorealism perspective and the theory of relative gains in examining this issue. This type of research is qualitative with descriptive data processing. Data collection as a reference in this study was carried out using the library method, namely utilizing secondary data obtained from various literatures such as books, journals, annual reports of several related agencies, official documents, and so on. The results of this study found that during the implementation of REDD+ in Indonesia, there were several challenges and obstacles that affected the effectiveness of the REDD+ work program. Norway's actions that did not realize the Result Based Payment (RBP) for Indonesia's success in reducing greenhouse gas emissions by 11.2 million tons of CO2eq and obstacles to REDD+ implementation were factors that caused Indonesia to terminate the REDD+ cooperation relationship because it was deemed not in accordance with Indonesia's national interests. Keywords: REDD+, Deforestation, Degradation, RBP